Effect of Liquid Phase Additions on Microstructure and Thermal Properties in Copper and Copper-Diamond Composites. (2nd December 2014) - Rape, A.; Liu, X.; Kulkarni, A.; Singh, J.
Abstract : This study details a new approach to creating copper-diamond composite materials for thermal management applications by using a two-phase (solid-liquid) approach in powder metallurgy using Field Assisted Sintering Technology (FAST). Silver-copper alloyed powder at eutectic compositions was used as a nonreactive liquid phase while Cu5 Si was used as a reactive liquid phase. Microstructure results are reported favorably comparing the additions of a small amount of liquid phase to pure solid state sintering. Additionally, EDX results indicate that the liquid phase material fills gaps at the interface of the matrix and diamond particle resulting in improved microstructure and density. Thermal conductivity results show that liquid phase additions improve the thermal conductivity of composites compared to composites without any liquid phase, but Si additions cause a severe drop in baseline conductivity.